Pengaruh Kebersihan Agregat terhadap Kuat Tekan Beton dan Implikasinya pada Konstruksi Struktural Sederhana - Sukadarminto, Sukadarminto; Anisarida, An An; Janizar, Syapril (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
Aggregate is the primary component of concrete, comprising 60–75% of its total volume; thus, its quality greatly influences the final performance of the concrete. Technical standards such as SNI 03-2834-2000 and ASTM C33/C33M recommend that aggregates be free from impurities such as silt and clay to ensure proper bonding and long-term durability. However, in small- to medium-scale construction, unwashed aggregates are still commonly used due to economic and logistical constraints. This study aims to evaluate the effect of aggregate cleanliness on compressive strength and explore its practical implications for low-rise residential buildings. The research was conducted through a laboratory experiment using two aggregate conditions (washed and unwashed), a mix ratio of 1:2:3, and compressive strength testing at 7, 14, and 28 days. The results indicate that concrete made with unwashed aggregates exhibited consistently higher compressive strength (by 0.9–1.1 MPa) compared to concrete with washed aggregates. This is likely due to a filler effect from fine particles that enhance the concrete’s density. However, high silt content may still compromise long-term durability. The findings suggest that locally sourced, unwashed aggregates could serve as an alternative for structural concrete in low-rise housing, provided proper quality control and technical validation are implemented.